Analisis High Order Thinking Skills (HOTS) Taksonomi Menganalisis Permasalahan Fisika - Syaiful Rochman; Zainal Hartoyo (SPEJ (Science and Physic Education Journal), 2018)
The purpose of this research is to get the measurement result as a description of higher order thinking skill in taxonomy to analyze physics problem in SMA XI class. This study is descriptive qualitative through three stages, namely: initial development of the instrument, content validation and empirical, and measurement. The research has been conducted in the region of Central Bengkulu Regency. The instrument used has been validated by the expert. An empirical valiadation test was conducted by 95 students. A valid instrument is used to measure student's higher order thinking skills. The number of learners measured using a total sampling of 148 learners. The measurement result shows very high analyze ability 1 student or 0,5 percent, ability analyze high 59 student or 40 percent, ability analyze analyze 62 student or 42 percent, ability analyze low 25 student or 17 percent, ability analyze very low 1 student or 0, 5 percent. On the average it can be concluded that higher order thinking skills on taxonomy analyze students in Bengkulu Tengah included in medium criterion. Keyword: HOTS, Analyze, Physics